2022
DOI: 10.3390/cells11101613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prenatal Glucocorticoid Exposure on Circadian Rhythm Gene Expression in the Brains of Adult Rat Offspring

Abstract: Circadian clocks control many vital aspects of physiology from the sleep-wake cycle to metabolism. The circadian clock operates through transcriptional-translational feedback loops. The normal circadian signaling relies on a ‘master clock’, located in the suprachiasmatic nucleus (SCN), which synchronizes peripheral oscillators. Glucocorticoid receptor (GR) signaling has the ability to reset the phase of peripheral clocks. It has been shown that maternal exposure to glucocorticoids (GCs) can lead to modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…This is an essential piece of evidence that might improve the understanding on how the circadian system adapts to jetlag or shift work. Our findings also suggest that the previously observed GCs-dependent modulation of light entrainment 25,53 , locomotor activity 54 and the cellular/molecular changes 44,55,56 , might also be a result from direct GCs feedback to the SCN.…”
Section: Discussionsupporting
confidence: 79%
“…This is an essential piece of evidence that might improve the understanding on how the circadian system adapts to jetlag or shift work. Our findings also suggest that the previously observed GCs-dependent modulation of light entrainment 25,53 , locomotor activity 54 and the cellular/molecular changes 44,55,56 , might also be a result from direct GCs feedback to the SCN.…”
Section: Discussionsupporting
confidence: 79%
“…In experimental animals, pulmonary fibrosis, osteoporosis, long bone growth impairment, and neonatal hypoglycemia were identified following prenatal DEX exposure ( Rivet et al, 2022 ; Wu et al, 2022 ; Xie et al, 2022 ; Zhang et al, 2022 ). Mechanistically, circadian rhythms, insulin-like growth factor 1 signaling, angiotensin II signaling, histone modifications, and dysregulation of miRNAs were responsible for long-term adverse presentations following DEX exposure ( Han et al, 2022 ; Liu et al, 2022 ; Madhavpeddi et al, 2022 ; Murray et al, 2022 ; Qiu et al, 2022 ). Thus, the benefits from prenatal DEX administration for autoimmune antibody-negative patients are still being debated.…”
Section: Discussionmentioning
confidence: 99%
“… Madhavpeddi et al (2022 ) demonstrated the involvement of angiotensin II in sex-selective cardiovascular function and autonomic changes in adult offspring exposed to DEX during the last 4 days of gestation in rats, which influenced the heart rate, heart rate variability, and mean arterial pressure. Murray et al (2022 ) indicated that prenatal exposure to DEX would affect circadian rhythm gene expression and impair the related molecular oscillators. Prenatal betamethasone therapy accelerates lung development in preterm infants but may induce early programming events with long-term cardiovascular consequences.…”
Section: Association Between Prenatal Drug Exposure and Programmed Ca...mentioning
confidence: 99%